DESAIN ULANG PRODUK TEMPAT TISSUE MULTIFUNGSI DENGAN MENGGUNAKAN METODE QUALITY FUNCTION DEPLOYMENT - Ginting, Rosnani; Batubara, Theresia Yosephin; Widodo, Widodo (TALENTA Publisher, 2017)
In human mindset changes along with the development of technology, trends and need for quality products increasingly demand the development of more complex product functions to meet the expectations of the product. Redesign the product made is a multifunctional tissue box. This product is intended for family or household needs. One of the methods that depart from consumer needs is the Quality Function Deployment commonly abbreviated as QFD. In this QFD quality control of a product based on the wants and needs of consumers. Characteristics of multifunctional tissue products obtained from the design objectives is the Multifunctional Tissue Box has a blue main function, has a main beam function, has a polkadot main function motif, has a main rectangular function hole, has a main function iron cover, has an ornament stickers, has an additional function of candy place, has additional color function pink, has additional functional stripe motifs and has additional iron functional material. Then get the best alternative with total cost Rp.75.895.